2023
DOI: 10.1101/2023.10.24.563466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Programs, Origins, and Niches of Immunomodulatory Myeloid Cells in Gliomas

Tyler E. Miller,
Chadi A. El Farran,
Charles P. Couturier
et al.

Abstract: Gliomas are incurable malignancies notable for an immunosuppressive microenvironment with abundant myeloid cells whose immunomodulatory properties remain poorly defined. Here, utilizing scRNA-seq data for 183,062 myeloid cells from 85 human tumors, we discover that nearly all glioma-associated myeloid cells express at least one of four immunomodulatory activity programs: Scavenger Immunosuppressive, C1Q Immunosuppressive, CXCR4 Inflammatory, and IL1B Inflammatory. All four programs are present in IDH1 mutant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…While IL-1β is among the most-well characterized inflammatory cytokines in GBM, TAMs secreting IL-1β support tumor growth [51][52][53][54][55][56][57][58] , and microglia (among other cell types) are enriched in an IL-1β inflammatory program 74 , it is still unknown whether TAMs secrete Wnt-5a and if a Wnt-5a-mediated crosstalk exists between TAMs and tumor cells. However, in addition to the known pro-migration and pro-invasion functions of Wnt-5a [59][60][61][62][63] , it has been reported that the expression of Wnt-5a in human glioma is positively correlated with the presence of TAMs 64 .…”
Section: Discussionmentioning
confidence: 99%
“…While IL-1β is among the most-well characterized inflammatory cytokines in GBM, TAMs secreting IL-1β support tumor growth [51][52][53][54][55][56][57][58] , and microglia (among other cell types) are enriched in an IL-1β inflammatory program 74 , it is still unknown whether TAMs secrete Wnt-5a and if a Wnt-5a-mediated crosstalk exists between TAMs and tumor cells. However, in addition to the known pro-migration and pro-invasion functions of Wnt-5a [59][60][61][62][63] , it has been reported that the expression of Wnt-5a in human glioma is positively correlated with the presence of TAMs 64 .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is important to note that the reciprocal interactions between glioma cells and the TME are continuously evolving from tumor initiation to progression and recurrence [188,189]. While the specific mechanisms underlying the evolution of glioma tumors remain to be solved, spatial transcriptomic and proteomic evidence has shown that glioma cells are dynamically reorganized into distinct regions that display unique molecular profiles or lineage states (e.g., proneural, mesenchymal, and classical) and are constantly adapting to evolving stresses from the surrounding TME [58,190]. Thus, the characterization of gliomas in patients cannot be a singular event and requires multiple regions and time points to be analyzed.…”
Section: Discussionmentioning
confidence: 99%